European Union’s Security Policy in the Digital Age. A Study of the Ban on Russian Media in Response to New Disinformation - Muhammad Nabil Rahdiga; Henny Saptatia Drajati Nugrahani (Journal of Social Research, 2024)
This research aims to explore the European Union’s (EU) security policies in the digital culture related to new threats of disinformation. Entering the Russian-Ukraine military conflict in early 2022, the EU believes that European society was facing new threats in the form of disinformation. The EU tightened sanctions against Russia related to the Ukrainian conflict, including sanctions against Russian media. The EU decided to ban the broadcast of Russian TV and Radio stations RT and Sputnik, as well as closing their offices in several EU member countries. This step was taken because the EU accused both media outlets of spreading disinformation and pro-Kremlin propaganda related to the conflict in Ukraine. The research was conducted using a qualitative method. Two theories were used in this research, namely Securitization Theory by Barry Buzan and Communicative Action Theory by Jurgen Habermas. Through Securitization Theory, researchers explore the EU’s action in constructing Russian media outlets as a threat to regional and global security and stability. Using Communicative Action Theory, researchers analyzes the EU’s actions in using certain communication and narratives to justify its policy towards Russian media outlets, and through this theory, researchers also question the legitimacy of the ban. The preliminary findings of this research show that the EU ban is controversial. Many parties accused the EU of restricting freedom of speech and limit the freedom of press. On the other hand, the EU maintains that this step is necessary to combat propaganda and disinformation, which are considered threats to national security and the integrity of the democracy in the EU